CIRI-CIRI BANGUNAN RUMAH INDIS DI KOTABARU YOGYAKARTA - , Tony Kunto Wibisono,Ir.; , DR. Ir. Arya Ronald. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Dutch colonial architecture in Indonesia is a unique phenomenon that occurs because of the mixing of cultures Holland with Indonesia's diverse culture, therefore the Dutch colonial architecture in various places in Indonesia have different and distinctive characteristics. Settlements in the Kotabaru was built at the end of World War I, as a modern residential complex consisting of homes are equipped with public facilities. The study was conducted with a qualitative case study methods. The study of the characteristics of the old building is done by using visual observation on the front facade of the old building with a focus on: Architectural elements of the mass of the main building and support, type of roof, the parts of the facade of the building, the direction of orientation and setback of buildings, using visual parameters Habraken (1987) which includes the spatial system, physical system and stylistic system. The findings obtained from this research process are: characteristics of the old colonial Dutch buildings in Kotabaru include: 1. The characteristic mass of the building, which contained: form a configuration of 2. two asymmetric mass then the mass asymmetric configuration. 3. The characteristic roof of the building, which are: combination asymmetry roof parent and a small roof then the combination symmetry of the parent and minor roof 4. The characteristics of the building facade, there are: breaking field facade and the use of open terrace 5. The characteristics of the building orientation and setback, which are: zoning areas for the direction of the orientation and extent of the building setback area. The results of the above study are expected to provide benefits for the conservation of old buildings, especially colonial Dutch in Yogyakarta Kotabaru.